Role of Biochemical Parameters for The Detection of Osteopenia of Prematurity - Paul, Shubhra Prakash; Das, Porimal Kumar; Shaha, Dhiman; Miah, Mamun; Akhter, Rawshan Jahan; Hoque, Mahbubul; Chowdhury, M A K Azad (Northern International Medical College Journal, 2024)
Background: Complications from preterm birth are the leading causes of death among children under 5 years of age, responsible for approximately 1 million deaths in 2015. Three-quarters of these deaths could be prevented with current, cost-effective interventions. Premature infants, particularly those born at <28 weeks of gestation, are at significant risk for reduced bone mineral content (BMC) and subsequent bone disease, variably termed metabolic bone disease (MBD), osteomalacia, osteopenia, or neonatal rickets. Risk of fracture and growth failure increase in the presence of osteopenia in these infants. Early detection of Osteopenia of Prematurity (OOP) may prevent unwanted deaths. Objectives: To identify biochemical markers of osteopenia in the neonatal period for early detection before the appearance of radiological evidence of osteopenia. Methods: This prospective observational study was carried out at Dhaka Shishu Hospital (DSH) from July, 2016 to June, 2018. Babies admitted in the Neonatal Intensive Care and Special Care Baby Unit with gestational age <34 weeks and birth weight <2200 gm were included in the study. Purposive sampling technique was used to collect the study data. Blood sample for baseline biochemical markers were collected in 1st week of life, then subsequently at 2 weeks interval up to corrected term age. Wrist radiography was done for to detect radiological osteopenia at 6th week post-natal age and at corrected term age. Then the biochemical parameters are compared with radiological osteopenia. Result: This study included 84 preterm new born below 34 weeks of gestation and a birth weight below 2200 grams. Radiological evidence of osteopenia of prematurity was found in 34 (40.5%) babies of which 29 (85.3%) were below 32 week and 5 (14.7%) were at or above 32 weeks. Osteopenic infants had significantly (p<0.001) lower birth weight (1318.82 ± 264.23 gm) compared to non-osteopenic infants (1701.40 ± 431.11 gm). Our study showed that the optimal cutoff point for Alkaline phosphatase (ALP) was 352.50 U/L at 3rd week of life, at which sensitivity and specificity were found 82.4% and 80.0% respectively. Serum inorganic phosphate values for the diagnosis of osteopenia was 4.67 mg/dl at 5th week of age. At this level, sensitivity was found to be 68.0%, whereas specificity was 60.0%. Serum calcium of the infants did not show any significant difference when they were enrolled in the study and in the first follow up. But serum calcium level was significantly lower in osteopenic infants compared to nonosteopenic infants in 2nd and 3rd follow up (p<0.05). Conclusion: High alkaline phosphatase level at 3rd week of life and low serum inorganic phosphate at 5th week of life can be used as a predictor of osteopenia of prematurity. Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 581-587